Acercamiento en las culturas pre-industriales (2020)
The human being's rationality started to be expressed through the construction of shelter and the primitive design of domestic objects. From the assessment of the structures and materials of an artificial nature, chronological relations of technical development are established as well as links between functions of different character: practical, communicative and formal aesthetic. The use of materials evolved, looking for the most appropriate shape for the efficient accomplishment of the function in order to build cities and to create the conditions for commerce, defense and war.